2013
DOI: 10.1080/03069885.2013.852158
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a Christian-based Grief Recovery Scale

Abstract: The purpose of this study was to develop and validate a Christian-based Grief Recovery Scale (CGRS) which was used to measure Christians recovering from grief after a significant loss. Taiwanese Christian participants were recruited from churches and a comprehensive university in northern Taiwan. They were affected by both the Christian faith and Chinese cultural beliefs. The CGRS is developed through replicated factor analyses in three stages. The final version of the CGRS retains 35 Likert-type items and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…These concepts powerfully impact Christian clients' responses to death and grief ( Chang, 2005 ). Previous research ( Tan, 2007 ;Pan, et al ., 2014 ) has indicated that bereaved persons were helped by religion and spirituality-related variables to deal with the depression more eff ectively than those who were not spiritually oriented. Through Christian faith, bereaved clients hold the hope that death is not the end ( Charles-Edwards, 2005 ).…”
Section: Grief In a Complex Cultural And Religious Contextmentioning
confidence: 90%
See 1 more Smart Citation
“…These concepts powerfully impact Christian clients' responses to death and grief ( Chang, 2005 ). Previous research ( Tan, 2007 ;Pan, et al ., 2014 ) has indicated that bereaved persons were helped by religion and spirituality-related variables to deal with the depression more eff ectively than those who were not spiritually oriented. Through Christian faith, bereaved clients hold the hope that death is not the end ( Charles-Edwards, 2005 ).…”
Section: Grief In a Complex Cultural And Religious Contextmentioning
confidence: 90%
“…As an example, open and public discussions of death are culturally forbidden for Chinese people year round (Hsu, Kahn, Yee, & Lee, 2004 ), including mainland China, Hong Kong, and Taiwan. In the spring season of the Chinese Lunar New Year, mentioning the matter of dying is extremely prohibited as well as in the ghost month of July in the summer season, in the fall season of the moon festival, and in the winter season of blessing with fi recrackers ( Pan, Deng, Tsai, Chen, & Yuan, 2014 ). Therefore, the topic of death remains one of the greatest societal taboos and is associated with bad luck ( Lee, 1997 ;Hsu, et al ., 2004 ;Ho, 2007 ).…”
Section: Grief In a Complex Cultural And Religious Contextmentioning
confidence: 99%